Performance of M-QAM MIMO PNC Based on MRC and ZR Techniques - Alaa A. Yassin; Ebtihal H. G. Yousif; Rashid A. Saeed; Hashim Elshafie; Abdullah Alenizi; Hesham Alhumyani (IEEE Open Journal of the Communications Society)
Wireless networks have been experiencing a very substantial increase in the delivered amount of data with high speed, due to the expansion of wireless applications. Physical-layer Network Coding (PNC) combined with MIMO techniques is introduced to optimize performance metrics and provide increased data throughput and full diversity gain. This paper investigates the performance of MIMO PNC assuming a Two-Way Relay Network (TWRN) over Rayleigh fading. Maximum Ratio Combining (MRC) and Zero-Forcing (ZF) for the receive/transmit diversity techniques are used at the relay node to reduce multi-user interference. The system model is based on denoise-and-forward (DNF) relaying along with the Latin Square (LS) mapping algorithm at the relay node and square M-ary Quadrature Amplitude Modulation (M-QAM) at all nodes. The targetted performance metrics are the error probability, improvement of uplink capacity gain and downlink achievable sum rate. Furthermore, the mathematical model of end-to-end and uplink average error probability, PNC throughput, capacity, and sum rate are derived for the proposed scheme over the Rayleigh fading channel and verified through Monte-Carlo simulations. The obtained result demonstrates the reduction of symbol error rate in addition to enhancement of the normalized throughput, capacity, and sum rate when increasing the number of antenna at the relay node.